Quantifying the Effect of the Built Environment on Surface Runoff using GIS and Remote Sensing: A Case Study of Ibex Hill-Lusaka - Nyimbili, Penjani Hopkins; Chalwe, Natasha; Kawimbe, Bwalya J; Lubilo, Foster; Mwanaumo, Erastus Misheng’u; Thwala, Wellington Didibhuku; Erden, Turan (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2023)
Flash floods are short-period floods with a high peak discharge. Flash floods may be brought about by an increase in rainfall coupled with the rise of impervious surfaces. Accurate estimation of surface runoff and flood depth is therefore a vital task in coming up with ways to intercept and manage excess surface runoff. The study was carried out in Salama Park – Ibex Hill of Lusaka City with a total area of 1,074,822m2. The research focused on quantifying the surface runoff for the years 2019 to 2021 using the Soil Conservation Curve Number (SCS-CN) method, Remote Sensing and GIS. The excess runoff was calculated to range between 306.787mm to 600.419mm and the flood depth computed ranged between 1.665m to 3.260m. The relevance of this study is to understand the mechanisms and examine the impact of excess surface runoff on the built environment as well as its associated consequences.